Yersinia pseudotuberculosis enterocolitis mimicking enteropathic γδ T-cell lymphoma with abnormal clonality - Imataki, Osamu (BioMed Central, 2014)
BACKGROUND: Yersinia pseudotuberculosis generally infects the gastrointestinal tract and causes enteropathy symptoms suggesting infection. Y. pseudotuberculosis infections are often complicated with intraceliac lymphoadenopathy mimicking malignant lymphoma. This is a first case of Yersinia pseudotuberculosis enteropathy mimicking enteropathic γδ T-cell lymphoma. This case highlighted the γδ T-cell reaction to Yersinia enterocolitis sometimes mimicking malignant lymphoma clinically. CASE PRESENTATION: A 72-year-old female was referred to our institute due to abdominal pain with skin rush, fever and diarrhea. Computed tomography (CT) scanning revealed mucosal swelling of the cecum with enlargement of regional lymph nodes. Laboratory data showed elevated CRP (7.74 mg/dL), an increased level of soluble interleukin-2 receptor (sIL-2R 3095 IU/mL), and CD3+ γδ T-cell circulation in peripheral blood and bone marrow (10.9% and 3.9%, respectively). Increased proportions of γδ T-cells supported the diagnosis of malignant lymphoma. Colonoscopy demonstrated hemorrhagic mucosal erosion with partial ulceration, and the subsequent pathological findings at the inflammation site suggested malignant lymphoma histopathology in the colon. These objective findings were entirely consistent with enteropathic γδ T-cell lymphoma. Thereafter, however, the microbiological results of the patient’s stool at admission showed Yersinia pseudotuberculosis, and she was diagnosed as having Yersinia enterocolitis. All abnormal findings including subjective symptoms were in remission or mitigated within 2 weeks after her onset. Even the γδ T-cell circulation disappeared (0.04% in peripheral blood), and we speculate that those cells were a reaction to the Yersinia infection. CONCLUSION: In this case, a differential diagnosis included infectious enterocolitis from other immunogenic or malignant diseases. Although a measurement of sIL-2R is critical in differentiating malignant lymphoma in patients suffering with lymph adenopathy, that is not confirmative. This patient’s case indicates that T cells expressing the γδ T-cell receptor might be associated with the acute and late phase reactions, in which T cells play a role in the construction of granulomas and the establishment of sequelae.